The Influence of Work Motivation on Nurse Performance at Elisabeth Hospital in Batam City - Novi Yulianti; Etty Sri Wahyuni (ALINEA: Health Science & Medical International Journal, 2025)
Background: Nurse performance is an essential component in improving the quality of healthcare services. One factor that may influence nurse performance is work motivation, which can encourage individuals to perform their tasks effectively and achieve organizational goals. Objective: This study aimed to examine the relationship between work motivation and nurse performance at Elisabeth Hospital in Batam City. Methods: This study employed a quantitative approach with a cross-sectional design. The study was conducted at Elisabeth Hospital in Batam City, involving 40 nurses selected using a total sampling technique. Data were collected using structured questionnaires measuring work motivation and nurse performance. Descriptive statistics were used to describe respondent characteristics, while the Chi-square test was used to determine the relationship between work motivation and nurse performance. Results: The results showed that most respondents had moderate levels of work motivation (60%), while 25% had high motivation and 15% had low motivation. In terms of performance, 65% of nurses demonstrated good performance, and 35% had moderate performance. Statistical analysis showed a significant relationship between work motivation and nurse performance (p = 0.021). Conclusion: Work motivation significantly influences nurse performance. Improving motivational factors within healthcare organizations may contribute to better nurse performance and improved healthcare service quality.